(NkURS SOLXFEDVIOs (NNOTAs - (Na(B. (Np(B. (NaGAVANOWs ((NsANKT(B-(NpETERBURGs (NlANXs (NpLANETA mUZYKIs, 2021)
(NsOLXFEDVIO(B-(NWAVNEJ[AQ DISCIPLINA MUZYKALXNOGO OBRAZOWANIQ NARQDU S \LEMENTARNOJ TEORIEJ MUZYKI GARMONIEJ POLIFONIEJ ANALIZOM MUZYKALXNYH PROIZWEDENIJ(B.s
Keywords: (NsOL_FEDVIOs